Financial Technology and Financial Inclusion in Remote Areas of Algeria. Analytical Study Using Data Mining - Hassiba Hadouga (Financial Markets, Institutions and Risks)
This study aimed to demonstrate how financial technology tools can be used to achieve financial inclusion by shedding light on the reality of financial technology and financial inclusion in Algeria, specifically in the remote areas of Algeria, as financial inclusion represents one of the main areas that economists and governments are trying to focus on to eliminate poverty. To reach the goal of the study, a statistical analysis method was adopted for the various questions asked to 200 participants in the survey during the period 2022–2023. A set of quantitative and qualitative data was used. The study population represents 200 individuals to whom the questionnaire was distributed. A data mining tool was used to analyze the study data, and the survey participants' K algorithm was later used to predict the behavior patterns of people from a similarly contextualized community regarding financial activities. The study concluded that financial technology, through its multiple tools, changes the structure of comprehensive financial services, in addition to the diversity and style of financial services provided to individuals, which has enhanced and increased their availability to a broader social group that did not have access to them. It was also shown that there is a significant impact of financial technology tools on enhancing financial inclusion indicators. It is recommended to adopt effective and modern financial and technological strategies that provide marginalized social groups with reasonable access to financial services and products that meet their needs, including transactions, payments, savings, credit, and insurance. Therefore, obtaining the added value of data and investing it will increase financial inclusion indicators.